Penyusunan Standard Operating Procedure (SOP) Evaluasi Perencanaan Perbekalan Kefarmasian di Rumah Sakit X - Purnamasari, Gusti Ayu Putu Prima; Noviyani, Rini (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2023)
Hospital Pharmacy Services is a health service that focuses on patients in providing quality, quality and affordable Pharmaceutical Preparations, Medical Devices, and Medical Consumables for the community. To ensure that pharmaceutical supplies are in accordance with the required quality and specifications, a planning process is necessary. From the results of interviews that have been carried out, that Hospital X has not evaluated the planning but is only planning to look at the disease pattern from the previous period. To overcome problems in the field, the preparation of Standard Operating Procedures (SOP) for evaluating pharmaceutical supply planning is carried out. Evaluation methods that can be used in planning are the ABC, VEN and PUT (ABC-VEN Combination) methods. Based on the Minister of Health Regulation Number 72 of 2016 the preparation of the SOP that has been made almost resembles the applicable laws and regulations and can be implemented properly at Hospital X so as to achieve adequate drug availability.